(untitled) (REMUNOM, 2025)
Inventory control can be the path for companies that seek better results with lower costs. Therefore, the objective is to identify and analyze the advantages of adopting the inventory control outsourcing process. The methodology used was descriptive bibliography with a qualitative background. The analysis of the results identified that outsourcing allows for a clearer and more integrated view of its logistics operations, increased security, quality and capacity in storage and distribution, optimization of physical space, reduction of losses, errors and operational costs, making it possible to consider that the Inventory outsourcing is accurate and efficient.